Toxicidade de Acaricidas sobre Diferentes Estágios de Vida de Tetranychus urticae Koch (Acari: Tetranychidae) em Mamoeiro - Esteves Filho, Alberto; Oliveira, José V.; Gondim Jr, Manoel G.C. (BioAssay, 2009)
The two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae), is one of the most important pests of papaya in Brazil. It causes leaf yellowing, necrosis, and leaf drop, reducing the papaya yield. In the present work, the effects of the acaricides fenpyroximate (50 g.L-1), lufenuron (50 g.L-1), tetradifon (80 g.L-1), azocyclotin (500 g.L-1), carbosulfan (200 g.L-1), dicofol (185 g.L-1), sulfur (800 g.kg-1), and chlorfenapyr (240 g.L-1) on eggs viability and adult female were tested at the 25, 50, and 75% ratios of recommended dosages from the commercial formulations. The effects of these acaricides at 75% ratio on the immature forms (larvae, protonymphs, deutonymphs) were evaluated also. Leaf discs (d (ø) = 3.5 cm), with 30 eggs each, were dipped into the respective treatments and distilled water (control) for 5 sec. All treatments were left to dry at room temperature for 30 min. For effects on adults, leaf discs were infested with 15 females each. Egg viability was determined after counting the number of living larvae at 96h after disc treatment. Adult mortality was evaluated after 72h of infestation and individuals were considered dead if they did not move when prodded with a fine pointed brush. The same method was applied to the active immature forms. The acaricides tetradifon, dicofol, and fenpyroximate were the most efficient in the control of eggs, while dicofol and azocyclotin were most efficient to control adult females. For the immature forms, activities of azocyclotin, chlorfenapyr, fenpyroximate, dicofol, and tetradifon are highlighted.